Associations of protein intake, sources and distribution on muscle strength in community-dwelling older adults living in Auckland, New Zealand. - Hiol AN; von Hurst PR; Conlon CA; Beck KL (Cambridge University Press, 2023)
Protein intake, sources and distribution impact on muscle protein synthesis and muscle mass in older adults. However, it is less clear whether dietary protein influences muscle strength. Data were obtained from the Researching Eating Activity and Cognitive Health (REACH) study, a cross-sectional study aimed at investigating dietary patterns, cognitive function and metabolic syndrome in older adults aged 65-74 years. Dietary intake was assessed using a 4-d food record and muscle strength using a handgrip strength dynamometer. After adjusting for confounders, in female older adults (n 212), total protein intake (β = 0⋅22, P < 0⋅01); protein from dairy and eggs (β = 0⋅21, P = 0⋅03) and plant food sources (β = 0⋅60, P < 0⋅01); and frequently consuming at least 0⋅4 g/kg BW per meal (β = 0⋅08, P < 0⋅01) were associated with higher BMI-adjusted muscle strength. However, protein from meat and fish intake and the coefficient of variance of protein intake were not related to BMI-muscle strength in female older adults. No statistically significant associations were observed in male participants (n = 113). There may be sex differences when investigating associations between protein intake and muscle strength in older adults. Further research is needed to investigate these sex differences.
Keywords: Muscle strength; Older adults; Protein distribution; Protein intake; Protein sources; Female; Male; Animals; New Zealand; Hand Strength; Cross-Sectional Studies; Independent Living; Muscle Strength; Eggs